PENDIDIKAN MODERASI BERAGAMA MELALUI PELATIHAN RETORIKA DAKWAH PADA MAJELIS TABLIGH PIMPINAN DAERAH AISYIYAH KABUPATEN GRESIK - Noor Amirudin; Muyasaroh Muyasaroh (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Dakwah in Islam is an invitation to do good that is moderate, of course in preaching it must pay attention to the rhetoric so that there are no elements of criticizing, vilifying, inciting and provoking between religions. Dakwah rhetoric is the art of speaking to influence others through dakwah messages. Dakwah rhetoric is a branch of communication science that discusses how to convey messages to others through the art of speaking so that dakwah messages can be received. Dakwah rhetoric can be interpreted as a speech or lecture that contains a dakwah message. This condition is a special concern for women from Aisyiyah Wringinanom Gresik Branch through a series of service activities with the theme Religious Moderation Education Through Dakwah Rhetoric Training at the Tabligh Assembly of the Aisyiyah Regional Leadership (PDA) Gresik Regency. The methods used in this service are lectures, discussions, brainstorming, and role-playing. The result of this service is that by holding dakwah rhetoric training for women preachers of the Tabligh PDA Council of Gresik Regency, they can be accustomed/trained and brave to become preachers both to just deliver dakwah personally, or to preach in general in the recitation while still paying attention to the principles of dakwah. that is in the rhetoric of dakwah.